Evaluation of Feed Consumption and Nutrient Adequacy of Different Breed Bulls at Artificial Insemination Centre – Lembang - Hadi, Sofwan (Unpad Press, 2023)
ABSTRACT This research was conducted to evaluate the feed consumption and nutrient adequacy of bull breeds at the Balai Inseminasi Buatan (BIB) Lembang. The study took place over a four-months, utilizing secondary data provided by the Artificial Insemination Centter (AIC) Lembang for the year 2021. The data used included number and breeds of bull, forage types , forage quality, concentrate quality, hay quality, dry matter consumption, protein consumption, and total digestible nutrients (TDN) consumption. The data were recorded monthly and accumulated to provide an average value for the one-year research period. The dry matter consumption of each feed type including both forage and concentrate, served as the basis for determining protein and TDN consumption.The Bull breeds were divided into two groups: large-type bull and small-middle-type bull. The data analysis results showed that the average dry matter consumption of forage and concentrate were 75.10% and 24.90%, respectively, for the large-type cattle and 76.49% and 23.51%, respectively, for the small-middle-type cattle. The total dry matter consumption was 1.16% of body weight for the large-type and 1.55% of body weight for the small-middle-type. The protein consumption for large-type and small-type cattle was 1760 g/head/day and 1520 g/head/day, respectively. These protein consumption values exceeded the NRC (National Research Council) standards by 32.12% and 40.29% for large-type and small-middle-type cattle, respectively. The TDN consumption for large-type and small-middle-type cattle was 7570 g/head/day and 6600 g/head/day, respectively. These TDN values were 17.05% and 26.02% higher than the NRC standards for large-type and small-middle-type cattle, respectively.The findings of this study conclude that the feed provided at the AIC Lembang exceeds the nutrient requirements of both types of male cattle.